A human keratin 14 "knockout": the absence of K14 leads to severe epidermolysis bullosa simplex and a function for an intermediate filament protein - Chan, Yujia A.; Anton-Lamprecht, Ingrun; Yu, Q. C.; Jäckel, Andreas; Zabel, B.; Ernst, J. P.; Fuchs, E. (Genes & development, 1994)
Since their discovery, the function of intermediate filaments (IFs) has remained obscure. In skin, epidermal cells have extensive cytoskeletal architectures of IFs, composed of type I and type II keratin heterodimers. Clues to possible functions of these proteins have come from recent studies showing that several autosomal-dominant, blistering skin disorders are caused by defects in genes that encode epidermal keratins. These diseases all exhibit cell degeneration and keratin network perturbations in cells that express the particular mutant keratin gene. However, it is not clear from these studies whether cytolysis arises from the presence of large insoluble keratin aggregates that compromise cellular physiology or from the absence of an extensive keratin filament network, which jeopardizes mechanical integrity. We report here the analysis of an extremely rare case of severe recessive epidermolysis bullosa simplex (EBS), where the patient lacks a discernible keratin filament network in basal epidermal cells. Genetic analyses revealed a homozygous point mutation that yielded a premature termination codon in the major basal type I keratin gene and caused complete ablation of K14. The consanguineous parents were normal, each harboring one copy of the null K14 mutation. Analysis of cultured keratinocytes enabled us to document that the loss of K14 is not compensated for by the up-regulation of any other type I keratin. When taken together with the in vivo studies showing the presence of cell fragility generated from the lack of an extensive basal keratin network, these findings provide the first clear demonstration of loss of function associated with the absence of an IF protein in vivo.